Numerical analysis of the angular insensitive photovoltaic light harvesting with the biomimetic scattering film inspired by the rose petal epidermal topography. (August 2018) - Li, Kan; Wu, Rengmao; Ruan, Yi; Zhang, Liuqing; Zhen, Hongyu
Graphical abstract: Highlights: Optical models based on bio-textures are built to predict PV device performance. The principles of light harvesting with biomimetic scattering films are explored. Thick silicon films and thin film organic solar cells are investigated. The optical optimization for thin film devices combines ray optics and wave optics. Abstract: Understanding the angular insensitive light harvesting principle is very important to the performance prediction and the optimal design of photovoltaic devices. A biomimetic scattering film was fabricated in our previous work by replicating rose petal epidermal topography with polydimethylsiloxane. It was experimentally proved that devices coated with this scattering film showed remarkable improvement in angular insensitive light harvesting. To further explore the principle behind it, a numerical analysis method was presented in this paper to evaluate the performance of photovoltaic devices with biomimetic scattering films. The parabolic cone array with disorder geometric parameters was used to approximate the real rose petal epidermal topography. Firstly, the optical properties of the bio-texture with geometrical disorders are investigated by means of ray tracing methods. Its light scattering ability, transmission and light trapping efficiency were quantified though a specific simulation model. Then, two types of photovoltaic devices were simulated, involving thick silicon films and thin film organic solar cells. It was concluded that the light harvesting was attributed to two aspects, the light trapping efficiency of the scattering film and the device absorption rate variation under scattering light illumination. By discussing these two factors separately, it turned out that the light trapping efficiency dominated the light harvesting for an absorber with low angular sensitivity like the thick silicon film; while for the one with high angular sensitivity such as organic solar cells, the two factors both made significant contributions. Furthermore, the angular insensitive light harvesting was mainly achieved by the stable light trapping efficiency under varied incident angles. At last, the simulation developed for thin film solar cells combined ray optics and wave optics. Thus, performance with different device structures can be optimized from the calculation. All the analysis methodology in this paper can give a guide on other types of bio-textures and various applications not limited to photovoltaics.